Lumbar Discectomy. Why Romanian Spine Surgeons and Neurosurgeons Need a Paradigm Shift? - Horatiu Alexandru MOISA; Dan Aurel NICA; Eugen Cezar POPESCU; Aurel George MOHAN; Gabriel IACOB; Alexandru Vlad CIUREA (Modern Medicine)
Low back pain and its management can be briefly summarized as an entire industry per se. As the general age of the population increases more and more patients find themselves hospitalized with degenerative disorders of the spine which might not always mandate surgery. This article wishes to illustrate the negative tendencies regarding the increasing number of patients frequently receiving ill-advised surgery for low back pain and the consequences that further implicate the healthcare system and the economy. At the same time the authors wish to highlight the need for a national database of patients operated for spine disease and discuss a few key-items spine surgeons and neurosurgeons need to consider prior to operating patients with degenerative diseases of the spine.